1999
DOI: 10.2307/1602721
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal and Infancy Home Visitation by Nurses: Recent Findings

Abstract: This article describes a 20-year program of research on the Nurse Home Visitation Program, a model in which nurses visit mothers beginning during pregnancy and continuing through their children's second birthdays to improve pregnancy outcomes, to promote children's health and development, and to strengthen families' economic self-sufficiency. The results of two randomized trials (one in Elmira, New York, and the second in Memphis, Tennessee) are summarized, and an ongoing trial in Denver, Colorado, is briefly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
297
0
8

Year Published

2000
2000
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 355 publications
(312 citation statements)
references
References 46 publications
7
297
0
8
Order By: Relevance
“…41 Home visiting by nurses has been shown consistently to reduce rates of childhood injury, to increase fathers' involvement, to reduce family welfare dependency, and to improve school readiness. 42 Housing subsidies have resulted in improved neighborhood safety and reduced exposure to violence. 43 In addition, clinic-based, literacypromoting programs that include the provision of children's books and anticipatory guidance about the importance of reading aloud with young children have been shown to enhance language development in toddlers 44 and preschoolers.…”
Section: How Can Schools and Communities Promote School Readiness?mentioning
confidence: 99%
“…41 Home visiting by nurses has been shown consistently to reduce rates of childhood injury, to increase fathers' involvement, to reduce family welfare dependency, and to improve school readiness. 42 Housing subsidies have resulted in improved neighborhood safety and reduced exposure to violence. 43 In addition, clinic-based, literacypromoting programs that include the provision of children's books and anticipatory guidance about the importance of reading aloud with young children have been shown to enhance language development in toddlers 44 and preschoolers.…”
Section: How Can Schools and Communities Promote School Readiness?mentioning
confidence: 99%
“…34 ā€¢ Professional or nurse-based home visiting is generally advantageous for clients. 35 The role of lay paraprofessional home visitors is less known, but paraprofessionals may be helpful depending on the goals and objectives of the home-visiting program and the length of engagement with the home visitor. An advantage of lay home visitors may be the notable cultural bond between the home visitor and mother.…”
Section: Benefits Of Home-visiting Programsmentioning
confidence: 99%
“…These studies suggest that parents experiencing high levels of stress may be less involved in and committed to the intervention, resulting in less positive outcomes (Kazdin and Wassell 1999;Lundahl et al 2006). However, other studies have shown that maternal depression, lack of psychological resources, low marital satisfaction, and low educational level were positively related to the effectiveness of parenting interventions (Beauchaine et al 2005;Berlin et al 1998;Lundahl et al 2006;Olds et al 1999;Olds and Korfmacher 1998;Reid et al 2003;van Zeijl et al 2006a). It may be that adverse family circumstances lead to increased intervention effectiveness, because these families are in greatest need of support (e.g., Beauchaine et al 2005).…”
Section: Introductionmentioning
confidence: 99%